ANALISIS SEKTOR EKONOMI UNGGULAN PADA KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Intan Saputri; Arfida Boedirochminarni (Program Studi Ekonomi Pembangunan, 2018)
This research aims to identify the leading sectors in South Sumatera Province. The analysis was conducted by comparing Gross Regional Domestic Product at Constant 2010 Price of Province of South Sumatra and Gross Regional Domestic Product at Constant 2010 Price Base of District in South Sumatera Province. The analysis model was Klassen Typology Analysis, and Location Quotient Analysis (LQ), Geographic Information System Analysis (GIS). The results of Klassen Typology analysis showed that the cities/regencies that belonged to fast-developed and fast-growing areas were Muara Enim and Palembang. The results of Location Quotient (LQ) analysis regencies of Ogan Komering Ulu showed that the potential to be the highest superior sectors between were the districts of Sounth Sumatera Province, they are agriculture, forestry and fishery sector, wholesale and retail trade sector; cars and motorcycles reparation sector, accomodation and refreshment provision sector, real estate sector, education services sector, Social Activities and Health sector, and other services sector. The results of Sistem Informasi Geografis (SIG) atau Geographic Informasi System (GIS) analysis showed that the agriculture, forestry and fishery sector the highest base sector in the city/district of Ogan Komering Ulu, Ogan Komering Ilir, Lahat, Musi Rawas, Banyuasin, Ogan Komering Ulu Selatan, Ogan Komering Ulu Timur, Ogan Ilir, Empat Lawang, dan Pagar Alam.Keywords: Gross Regional Domestic Product, Agriculture Sector, Trading Sector, and Accommodation Sector